2017
DOI: 10.1016/j.amjcard.2017.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Changes in Body Fat Distribution to Oxidative Stress

Abstract: Android fat is a surrogate measure of visceral obesity in the truncal region. Both visceral adiposity and oxidative stress (OS) are linked to cardiometabolic risk factors and clinical cardiovascular disease. However, whether body fat distribution (android vs gynoid) is associated with OS remains unknown. We hypothesized that increased android fat will be associated with greater OS. Body fat distribution and markers of OS, including plasma levels of reduced (cysteine and glutathione) and oxidized (cystine and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Heval et al reports that glutathione concentration correlates inversely with the amount of various fat deposits, such as gynoid fat, android fat, and total fat. 65 Xiao et al reported that SOD correlated negatively with the VAF area. 18 Nevertheless, we found no correlation between enzymatic antioxidants and VAF volume.…”
Section: Discussionmentioning
confidence: 99%
“…Heval et al reports that glutathione concentration correlates inversely with the amount of various fat deposits, such as gynoid fat, android fat, and total fat. 65 Xiao et al reported that SOD correlated negatively with the VAF area. 18 Nevertheless, we found no correlation between enzymatic antioxidants and VAF volume.…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we are aware, well-controlled lutein supplementation is not common, and this study will be the only study of its type to be conducted in the context of central obesity. Central obesity is a state of chronic lowgrade inflammation characterised by elevated concentrations of circulating inflammatory markers, which may be a critical link between metabolic disorders such as IR and diabetes [12,33]. Therefore, individuals with central obesity also deserve attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we are aware, well-controlled lutein supplementation is not common, and this study will be the only study of its type to be conducted in the context of central obesity. Central obesity is a state of chronic lowgrade inflammation characterized by elevated concentrations of circulating inflammatory markers, which may be a critical link between metabolic disorders such as IR and diabetes [12,33]. Therefore, individuals with central obesity also deserve attention.…”
Section: Discussionmentioning
confidence: 99%